RISK ANALYSIS OF WORK POSTURE ON COMPLAINTS OF MUSCLE MOVEMENT DISORDERS (GOTRAK) BASED ON SNI 9011: 2021 IN THE PACKING PLAN UNIT INDARUNG PT SEMEN PADANG - Rafika Sari, Dina; Duana, Maiza; Putra, Onetusfifsi; Is, Jun Musnaidi; Wintah, Wintah (HEARTY, 2025)
Complaints of skeletal muscle disorders are disorders of skeletal muscles with low, medium and high risk levels that can interfere with workers resulting in work accidents and occupational diseases. Therefore, this study is to see the relationship between factors associated with GOTRAK complaints in packer and transport (loading) workers in the Indarung Packing Plan Unit of PT Semen Padang. This study used a quantitative analytical method with a cross-sectional design and filling out a GOTRAK complaint survey in accordance with SNI 9011: 2021. While primary data is obtained from video recordings when workers do work. The results of statistical tests with the chi-square test stated that there was a relationship between GOTRAK complaints and work position (p-value=0.001, length of work (p-value=0.001), physical fatigue (p-value=0.001), and pain (p-value=0.001). The survey results of GOTRAK complaints SNI 9011: 2021 showed a number 4 with a moderate risk level so that it requires improved work regulations and improved workplace design. 38 workers in the packer and transport (loading) section experienced GOTRAK complaints.